2020
DOI: 10.1002/jum.15424
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Perfusion Analysis of Quadriceps, Patellar, and Achilles Tendon Regeneration With Dynamic Contrast‐Enhanced Ultrasound and Dynamic Contrast‐Enhanced Magnetic Resonance Imaging

Abstract: Objectives The healing process of tendons after surgical treatment of tendon ruptures mainly depends on the perfusion of the tendon and its surrounding tissue. Dynamic contrast‐enhanced ultrasound (DCE‐US) and dynamic contrast‐enhanced MRI (DCE‐MRI) can provide additional information about the local microperfusion. In this pilot study, the feasibility of these techniques to assess the vascularization during tendon regeneration was evaluated. Methods Between 2013 and 2015, 23 patients with surgical treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Their most recent work also demonstrated that dynamic CEUS could be used to visualize the microperfusion of healing tendons using parameters such as PE, WiAUC, and TTP with a strong correlation with dynamic contrast-enhanced MRI. [ 51 ]…”
Section: R Esults and Discussionsmentioning
confidence: 99%
“…Their most recent work also demonstrated that dynamic CEUS could be used to visualize the microperfusion of healing tendons using parameters such as PE, WiAUC, and TTP with a strong correlation with dynamic contrast-enhanced MRI. [ 51 ]…”
Section: R Esults and Discussionsmentioning
confidence: 99%
“…The most important role of this imaging method is in cancer diagnosis and aftercare [ 31 , 32 ]. Fischer et al demonstrated in a pilot study that CEUS is a feasible method for assessing microperfusion in a reconstructed tendon [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical 39 and clinical 40,41 studies have in fact reported strong associations between contrast‐enhanced sonography and DCE‐MRI derived perfusion parameters in characterizing cancers, and healing tendons. Similarly, some studies have reported strong positive correlations between Doppler sonography and DCE‐MRI derived perfusion parameters 42,43 .…”
Section: Discussionmentioning
confidence: 99%